Pengaruh Perceived Ease of Use terhadap Behavioral Intention Penggunaan TikTok Shop pada Mahasiswa - Larasati, Adillia; Sefira, Dinda Putri; Wibowo, Cheyzha Febri Ananta; Rohim, Najwa Ulya; Kurniawan, Dendy Bagus; Nugraha, Joko Tri (FIA Unkris Press, 2026)
This study aims to analyze the influence of Perceived Ease of Use on Behavioral Intention of TikTok Shop use in students. The method used in this study is quantitative with an associative approach. The variables of this study consist of PEOU independent and BI dependent variables. The data was obtained through the distribution of a Likert scale questionnaire to students of FISIPOL Tidar University. The study population was students using TikTok Shop, with a sample of 91 respondents determined using the Slovin formula at a margin of error of 5%. The sampling technique used was probability sampling with the criteria that respondents had used TikTok Shop. The resulting data analysis included validity, reliability, and simple linear regression tests using SPSS 31.0. And the results showed that all instruments were valid and reliable with a Cronbach's Alpha value of > 0.60. The regression test showed that PEOU had a positive and significant effect on BI with a significance value of 0.001 (<0.05) and a determination coefficient of 0.593. This means that 59.3% of BI variations are explained by PEOU. In conclusion, the higher the perception of ease of use, the higher the intention of students to use TikTok Shop.